Leading towards Islamic Tourism City by managing the sensitivity of society: a case study of Terengganu - Ruzulan, Zulaipa; Jamaludin, Mohammad Aizat; MFH, Hanifah; Saidon, Rafeah (The Mattingley Publishing Co., Inc., 2020)
Terengganu is one of the states in Malaysia with a unique identity that can attract local and foreign tourists. The state has been very welcoming towards tourists, which has made them an attractive Islamic tourist destination in 2018. To retain its reputation, the state government needs to ensure proper planning and strategies in ensuring the Islamic principles are implemented accordingly. Thus, this study aims to examine the significant factors for the success of Terengganu as an Islamic tourism city in managing the sensitivity of society. To achieve this objective, a qualitative research methodology which consists of text document was used, and then the data were analyzed by using content analysis and constant comparative techniques. The results have shown that the sensitivity of the local society has been taken into consideration by Terengganu's state government. In ensuring the preservation of the image of the Islamic state, the government needs to consider the sensitivity of the Muslim society in governing the Islamic tourism city.